2015
DOI: 10.3389/fpls.2015.01157
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulatory Network Analysis of MYB Transcription Factor Family Genes in Rice

Abstract: MYB transcription factor (TF) is one of the largest TF families and regulates defense responses to various stresses, hormone signaling as well as many metabolic and developmental processes in plants. Understanding these regulatory hierarchies of gene expression networks in response to developmental and environmental cues is a major challenge due to the complex interactions between the genetic elements. Correlation analyses are useful to unravel co-regulated gene pairs governing biological process as well as id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 94 publications
4
49
0
Order By: Relevance
“…To the same extent as for NAC genes, these numbers globally match to the ones previously described for these species. One hundred ninety-seven (Katiyar et al, 2012), 198 (Yanhui et al, 2006, and 133 (Li et al, 2016) MYB genes were identified in Arabidopsis, 191 in poplar (Wilkins et al, 2009),141 in eucalyptus (Soler et al, 2015), 155 in barrel medic (Zhong and Ye, 2015), 157 in maize (Du et al, 2012), 209 in foxtail millet (Muthamilarasan et al, 2014), 233 (Smita et al, 2015), 155 (Katiyar et al, 2012), and 163 (Yanhui et al, 2006) MYB in rice and 122 in brome (Zheng et al, 2017).…”
Section: Phylogenetic Analyses Of the Myb Transcription Factor Familymentioning
confidence: 99%
“…To the same extent as for NAC genes, these numbers globally match to the ones previously described for these species. One hundred ninety-seven (Katiyar et al, 2012), 198 (Yanhui et al, 2006, and 133 (Li et al, 2016) MYB genes were identified in Arabidopsis, 191 in poplar (Wilkins et al, 2009),141 in eucalyptus (Soler et al, 2015), 155 in barrel medic (Zhong and Ye, 2015), 157 in maize (Du et al, 2012), 209 in foxtail millet (Muthamilarasan et al, 2014), 233 (Smita et al, 2015), 155 (Katiyar et al, 2012), and 163 (Yanhui et al, 2006) MYB in rice and 122 in brome (Zheng et al, 2017).…”
Section: Phylogenetic Analyses Of the Myb Transcription Factor Familymentioning
confidence: 99%
“…The expression correlation of the PheHsfs was calculated by Pearson correlation coefficient (PCC; R-value) using gene expression RPKM values from the high-throughput transcriptome data in R. Expression correlation data were used for the correlation network, and co-expressed gene pairs were filtered with a PCC cut-off of 0.85 as previously described [50]. Cytoscape version 3.4.0 were used to analyze and visualize the network [51].…”
Section: Co-expression Network and Protein Interactions Of Phehsfsmentioning
confidence: 99%
“…NLP3 (LOC_Os01g13540) played a major role in nitrate uptake, translocation and signaling in rice root [66]. Both LOC_Os01g13570 [67] and LOC_Os01g13740 [68] participated in abiotic stress response. Similarly, in the qFLL 2.1 region, three candidate genes including OsbZIP19 (LOC_Os02g14910), OsCNGC1…”
Section: Discussionmentioning
confidence: 99%